ELEMENTS RESOURCE POTENTIAL IN TAILINGS AT THE TAILING STORAGE FACILITY OF PT. INDONESIA CHEMICAL ALUMINA (PT. ICA), TAYAN DISTRICT, SANGGAU REGENCY, WEST KALIMANTAN - Eka, Eka; Setiawati, Septami; Sitorus, Berlian (Jurnal Teknik Sipil, 2023)
PT Indonesia Chemical Alumina (ICA) is the first Chemical Grade Alumina (CGA) producer company in Indonesia which produces tailings, namely red mud, with ± 30% water content and stored in class III landfill facilities according to PP 101 of 2014 article 146. The stockpile has been mixed with tailing from thermal power station (PLTU) of PT ICA which are fly ash and bottom ash (FABA). This study aimed to determine the area and volume of the pile, analyze the characteristics of the tailings, and identify the potential elemental counts in PT ICA's tailings. The method used is mapping using the DJI Mavic 3 Pro, composite sampling, cone and quartering, and characterization using XRF. The results obtained from drone data were converted to determine the amount of potential in each element. The area and volume of tailing pile are 5.64 hectares and 1,400,459.96 tons. The results of the XRF analysis show that the highest elements and oxide compounds are Fe and Fe2O3 at 69.74% and 60.26%, respectively.